Rationale for Necessity of Continuing Dental Education Program among Practicing Dentist: A Double Blind Study - Ramesh, AS; Prakash, R (Journal of Orofacial Research, 2012)
It is common knowledge, senior practitioners think that their practice keeps them well-acquitted with knowledge and skill and that they do not need any Continuing Dental Education (CDE) program. They think such CDE programs are only for junior practitioners. Aims: This paper was done to investigate the relation between the seniority of practice and their need for CDE programs. To this end, the skill level of both senior and junior practitioners was analyzed. Materials and methods: Casts of various dental surgeon around Chennai were collected from reputed dental technicians. A photograph of the prepared tooth was made. Using software ‘Image tool’ the taper of the prepared tooth was determined. Then the results were analyzed. Result: The result show that the junior practitioners had a mean taper of 17.3402 with a max taper of 23.15 and a min taper of 14.07. Senior practitioners had a mean taper of 21.3420 with a max taper of 24.13* and a min taper of 15.22. Conclusion: Analysis of the result shows interesting data, which leads to the conclusion that senior practitioners need CDE program as much as the junior practitioners.